Using digital technology to enhance formative assessment in mathematics classrooms - Dalby, D.M.; Swan, Malcolm (Wiley, 2018)
In this paper, which is based on research from the EU-funded project Improving Progress through Formative Assessment in Science and Mathematics Education (FASMEd), we explore how iPads are used within formative assessment processes by six mathematics teachers and their classes in two secondary comprehensive schools in the Midlands of England. A design research approach is first used to develop and trial six lessons in which iPads are used in different ways within formative assessment processes. Through lesson observations, video analysis and teacher interviews we then examine how iPad technology contributes to these processes, the functions it performs and the distribution of activity between the main actors (teacher, technology and student). An analytic approach is developed which captures the interactions in visual representations, showing how the technology is often used as a form of communication but also performs more active functions which affect the role taken by the teacher in formative processes. The study offers insight into ways in which iPad technology contributes to effective student learning through formative assessment and introduces an analytic approach that may be useful for further studies.